Flexural and shear strengthening of concrete structures with prestressed GFRP sheets - Ahmad, Syed Iftikhar (University of Ottawa (Canada), 2006)
Although Carbon Fibre Reinforced Polymer (CFRP) composite sheets have showed excellent results in laboratory for strengthening reinforced concrete structures, it could not get wide popularity in field application cost. To address this problem the present study was carried out to explore the possibility of using Glass FRP (GFRP) composite sheets which is relatively cheap material. GFRP has relatively low modulus of elasticity and therefore disregarded for strengthening in the past. Active strengthening technique i.e. prestressing was used for maximum utilization of GFRP strength. Prestressing has not only helped in achieving this goal but also improved the behaviour of strengthened member under service load and delayed premature delamination. Long term losses associated with prestressing were also studied and it was found in acceptable range. The research work comprised of both experimental and analytical investigations. The experimental program consisted of testing twenty three (eight flexure and fifteen shear), rectangular section, simply supported reinforced concrete beams. The variables in flexure beams were levels of prestressing, number of GFRP layers, and conventional reinforcement ratio. In shear beams variables were shear span to effective depth (a/d) ratio, number of prestressed GFRP layers, non-prestressed GFRP U-straps and U-jackets. Flexure beams strengthened with prestressed GFRP sheet showed higher increase in flexural capacity and better serviceability behaviour. Shear beams strengthened with prestressed GFRP sheets showed increase in shear capacity. Delay in sheet delamination was noted in prestressed GFRP sheet. Long term retention of prestressing force in GFRP sheets was noted in strengthened beams. An innovative and easy to apply prestressing system was developed in this study. Recommendation was framed for modification in the prestressing system for field application. The analytical tool i.e. Response 2000, used in this study accurately predicts the flexural beam behaviour whereas prediction of shear capacity was underestimated due to ignoring the effect of transverse clamping force on shear capacity. For the rest of shear beams, the model accurately predicted the shear capacity. Comparison of predicted and observed results of shear and flexure beams was carried out and it was concluded that prestressing of GFRP sheet is a useful and economical technique for strengthening of structural members.
Keywords: Engineering, Civil.